A DedA Family Membrane Protein Is Required for Burkholderia thailandensis Colistin Resistance - Panta, Pradip R.; Kumar, Sujeet; Stafford, Caroline F.; Billiot, Caitlin E.; Douglass, Martin V.; Herrera, Carmen M.; Trent, M. Stephen; Doerrler, William T. (Frontiers in Microbiology, 2019)
Colistin is a “last resort” antibiotic for treatment of infections caused by some multidrug resistant Gram-negative bacterial pathogens. Resistance to colistin varies between bacterial species. Some Gram-negative bacteria such as Burkholderia spp. are intrinsically resistant to very high levels of colistin with minimal inhibitory concentrations often above 0.5 mg/ml. We have previously shown DedA family proteins YqjA and YghB are conserved membrane transporters required for alkaline tolerance and resistance to several classes of dyes and antibiotics in Escherichia coli. Here, we show that a DedA family protein in B. thailandensis (DbcA; DedA of Burkholderia required for colistin resistance) is a membrane transporter required for resistance to colistin. Mutation of dbcA results in >100-fold greater sensitivity to colistin. Colistin resistance is often conferred via covalent modification of lipopolysaccharide (LPS) lipid A. Mass spectrometry of lipid A of ∆dbcA showed a sharp reduction of aminoarabinose in lipid A compared to wild type. Complementation of colistin sensitivity of B. thailandensis ∆dbcA was observed by expression of dbcA, E. coli yghB or E. coli yqjA. Many proton-dependent transporters possess charged amino acids in transmembrane domains that take part in the transport mechanism and are essential for function. Site directed mutagenesis of conserved and predicted membrane embedded charged amino acids suggest that DbcA functions as a proton-dependent transporter. Direct measurement of membrane potential shows that B. thailandensis ΔdbcA is partially depolarized suggesting that loss of protonmotive force can lead to alterations in LPS structure and severe colistin sensitivity in this species.